Cannabis use: A look at different factors and a reflection on its susceptibility to work-related accident - Francois GD Beaulieu; Mahée Coté (Forensic Science Today - Peertechz Publications, 2023)
Misinformation and popular beliefs on cannabis use have had an impact on the Canadian population. The trivialization of the substance and poor understanding of its side effects tend to add to the risks of work-related environments that already require acute senses and sharp attention. In this research project, we aim to observe different concurrent factors of cannabis use in Canada and how it articulates with the rising rates of work-related accidents. Since recreational cannabis use has been legalized, and with the onset of the COVID-19 pandemic, more people appear to be consuming and/or appear to have increased their usage. We will take a closer look at the impact of these factors, the role that misinformation plays on cannabis use, and how we can contribute towards healthier and safer working environments in Canada.